Pattern of Congenital Heart Diseases among Term and Preterm Neonates in a Tertiary Care Hospital of a Developing Country - Fahim Ahmed Subhani; Abdul Wahab Siddique; Ammara Ayub; Bilal Ahmed; Syed Awais ul Hassan Shah; Asma Anjum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency and pattern of various congenital heart diseases in a tertiary care hospital neonatal unit.